POOLED ESTIMATES OF INCIDENCE OF ENDOPHTHALMITIS AFTER INTRAVITREAL INJECTION OF ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR AGENTS WITH AND WITHOUT TOPICAL ANTIBIOTIC PROPHYLAXIS. Issue 1 (January 2018) - Reibaldi, Michele; Pulvirenti, Alfredo; Avitabile, Teresio; Bonfiglio, Vincenza; Russo, Andrea; Mariotti, Cesare; Bucolo, Claudio; Mastropasqua, Rodolfo; Parisi, Guglielmo; Longo, Antonio
Abstract : Purpose: To assess the effect of topical antibiotic prophylaxis on postoperative endophthalmitis after intravitreal injection of anti–vascular endothelial growth factor agents. Methods: A systematic literature search was performed from inception to March 2016 using PubMed, Medline, Web of Science, Embase, and the Cochrane Library, to identify articles that reported cases of endophthalmitis after intravitreal injection of anti–vascular endothelial growth factor agents. We used a pooled analysis to estimate the incidence of cases of endophthalmitis who developed after injections performed with and without topical antibiotic prophylaxis. We used regression analysis to explore the effects of study characteristics on heterogeneity. Results: From our search of electronic databases, we identified and screened 4, 561 unique records. We judged 60 articles to have reported findings for cohorts of patients who met our inclusion criteria, (12 arms of randomized clinical trials, 11 prospective cohort studies, and 37 retrospective cohort studies), which included 244 cases of endophthalmitis and 639, 391 intravitreal injections of anti–vascular endothelial growth factor agents. The final pooled estimate endophthalmitis proportions were 9/10, 000 (95% confidence interval, 7/10, 000–12/10, 000) in the antibiotic-treated group and 3/10, 000 (95% confidence interval, 2/10, 000–5/10, 000) in the untreated group. The estimated incidence of endophthalmitis with topical antibiotic prophylaxis was approximated three times the incidence without prophylaxis. Random effects regression showed that none of the study characteristics significantly affected the effect size in either group. Conclusion: Topical antibiotic after intravitreal injection of anti–vascular endothelial growth factor agents is associated with a higher risk of endophthalmitis. Abstract : Supplemental Digital Content is Available in the Text.Pooled estimates of the risk of endophthalmitis after intravitreal anti-VEGF agents were approximately three times as great with topical antibiotics given prophylactically as without them.